THE PERCEPTION OF LOVE IN “THAT I DID ALWAYS LOVE” BY EMILY DICKINSON AND “LOVE AFTER LOVE” BY DEREK WALCOTT - Roesitha Dewi Mike Syuriadi (LINGUAMEDIA Journal, 2022)
The goal of this study was to learn more about the perception of love in “That I Did always Love” by Emily Dickinson and “Love after Love: by Derek Walcott. The research method used is the descriptive-qualitative method. Abrams theory becomes the main key in this research. The results of this research showed that the perception of Emily Dickinson about love in her poem “That I did always Love” that Life is nothing without love. She forces to have love and it must happen into her life. Because she desires to be loved, wanted, needed, missed, and prioritized by the man she wants. Where in real life she has never felt what love is. Therefore she seems so desperate to feel and get love. In contrast to Derek Walcott's perception of love in his poem “Love after Love”, he considers that there is no need to rush into looking for love; he wants all his readers to focus more on improving themselves and loving themselves and allowing true love to find them.